Microstructural evolution analysis of grains and tensile properties of tin bronze in hot extrusion at different temperatures. (2nd January 2019) - Hui, Jun; Feng, ZaiXin; Wang, Pengfei; Fan, Wenxin; Liu, Zhuang
Abstract: In this paper, Electron Back-Scattered Diffraction is adopted to analyze the tin bronze microstructural changes of grains and grain boundaries in hot extrusion from 620 to 720°C. The result shows that the size of grains grows as the temperature rises with a competitive status between recrystallisation and subgrains and deformed grains, and shows a random distribution with no obvious preferred orientation in structure. High angle grain boundaries (>30°) are most common with a large quantity of Σ3 boundaries at 60°. Twin grains firstly appear in recrystallisation and grow continuously at subgrains. In the tensile test, re-crystallised grains had certain influence on the plasticity of tin bronze. Along with the elongation of tin bronze at temperatures above 700°C, its plasticity also declined.